ANALISIS MOTIVASI INTERNAL DAN EKSTERNAL DALAM MENINGKATKAN KINERJA PEGAWAI BADAN PENGELOLA PENDAPATAN DAERAH KABUPATEN BARITO UTARA - Fie Khaeriyah (Sekolah Tinggi Ilmu Ekonomi Muara Teweh, 2025)
This study aimed to analyze the influence of internal motivation (X1) and external motivation (X2) on employee performance (Y). The research method employed multiple linear regression analysis using questionnaire data processed through SPSS 27.0. Validity and reliability tests confirmed that all items were valid (item-total correlation > 0.279) and the instrument was reliable (Cronbachâ€™s Alpha = 0.903). Classical assumption tests proved the data were free from multicollinearity (VIF < 10), heteroscedasticity (random scatterplot), normality (Kolmogorov-Smirnov Asymp. Sig. 0.200 > 0.05), and autocorrelation (Runs Test Sig. 0.568 > 0.05). Regression analysis yielded the equation: Y = 7.678 + 0.245X1 + 0.435X2. The F-test (simultaneous) demonstrated that both variables significantly influenced performance (F-statistic = 17.203 > F-table = 3.19; Sig. 0.000). The t-test (partial) revealed that only external motivation had a significant effect (t-statistic = 3.096 > t-table = 2.012; Sig. 0.003), while internal motivation was insignificant (t-statistic = 1.821 < 2.012; Sig. 0.075). The coefficient of determination (RÂ² = 42.3%) indicated a moderate contribution of the independent variables to performance. In conclusion, external motivation was the dominant factor affecting employee performance. Recommendations for organizations include enhancing external reward systems and improving the work environment, while future researchers are advised to explore additional factors such as organizational culture.